2022
DOI: 10.15252/embr.202254721
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of epigenetic resistance to HDAC inhibitors in dystrophic fibro‐adipogenic progenitors

Abstract: Pharmacological treatment of Duchenne muscular dystrophy (DMD) with histone deacetylase inhibitors (HDACi) is currently being tested in clinical trials; however, pre‐clinical studies indicated that the beneficial effects of HDACi are restricted to early stages of disease. We show that FAPs from late‐stage mdx mice exhibit aberrant HDAC activity and genome‐wide alterations of histone acetylation that are not fully reversed by HDACi. In particular, combinatorial H3K27 and/or H3K9/14 hypo‐acetylation at promoters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“… 14 , 29 This has been associated with FAPs exhibiting aberrant HDAC activity with genome-wide alterations of acetylation, and with a senescent state of FAPs that are not fully reversed by the epigenetic molecules. 30 Thus, functional heterogeneity between FAPs from the supra- and infraspinatus muscles, associated with injury stage, may influence the mechanisms through which vorinostat modulates tissue repair, and consequently modify the FAP-satellite cell relationship. This indicates the importance of a permissive environment within regenerating muscles for the beneficial action of vorinostat, suggesting that our RC injury model develops a disease-associated resistance in the late stages of injury that might limit the efficacy of the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 29 This has been associated with FAPs exhibiting aberrant HDAC activity with genome-wide alterations of acetylation, and with a senescent state of FAPs that are not fully reversed by the epigenetic molecules. 30 Thus, functional heterogeneity between FAPs from the supra- and infraspinatus muscles, associated with injury stage, may influence the mechanisms through which vorinostat modulates tissue repair, and consequently modify the FAP-satellite cell relationship. This indicates the importance of a permissive environment within regenerating muscles for the beneficial action of vorinostat, suggesting that our RC injury model develops a disease-associated resistance in the late stages of injury that might limit the efficacy of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the transcription factors Mef2 and MyoD are acetylated during myogenic differentiation, and their acetylation promotes myogenesis, 35 while non-histone acetylation increases have been detected in specific gene promoters in FAPs. 30 Moreover, the overall outcome of subjecting FAPs and satellite cells to systemic vorinostat exposure may hinge on a complex interplay of direct and indirect effects, with signals originating from other muscle-resident cell types concurrently exposed to vorinostat. 36 According to this idea, vorinostat has the capacity to act on inflammatory cells, reducing the production of proinflammatory cytokines, 37 which modulate FAP-satellite cell interaction in an injury stage-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that HDACi have an influence on the activity of other cell types present in the muscle tissue, such as fibro-adipogenic progenitors and muscle stem cells. 31 The altered microenvironment influenced by HDACi might improve general muscle tissue health and, concomitantly, result in improved delivery of the ASO and/or recovery of ASO-induced dystrophin protein. This potential positive effect of HDACi + VPA is not properly mimicked in the homogeneous in vitro myocyte cultures, potentially explaining why this model does not benefit from HDACi in similar fashion to our in vivo model system.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of HDAC2, by using the class I HDAC inhibitor MS-275 or siRNA, restores the level of global HDAC activity similar to healthy control muscles, leading to morphological and functional benefits in dystrophic muscles [124]. In more recent studies, increased activity of class I, class IIa and class I/IIb HDACs in muscles of 1.5-month-old mdx mice [27] and in Fibro-Adipogenic Progenitors (FAPs) isolated from 1.5 month-and 12 month-old mdx mice has been reported [167], further suggesting the involvement of HDACs in the pathogenesis of DMD.…”
Section: Targeting Histone Deacetylases In Muscular Dystrophiesmentioning
confidence: 99%